2003
DOI: 10.1063/1.1635980
|View full text |Cite
|
Sign up to set email alerts
|

Disk substrate deposition techniques for monodisperse chemically synthesized FePt nanoparticle media

Abstract: Self-assembled FePt nanoparticles hold promise for future ultrahigh-density magnetic recording media because of their high anisotropy and capability to be formed into small and uniform grains. By using a special spin coater, we were able to form a dense array of FePt particles across the entire surface of a 2.5 in. disk substrate. Our method can control the number of layers of FePt nanoparticles. The media deposited with FePt nanoparticles by the spin coater was annealed in a vacuum. We measured read–write pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…Metal nanoparticles and other metal nanostructures are the basic building blocks in photonics research 12 and it is expected that magnetic nanoparticles will have a dramatic impact on high density magnetic recording 13 and radarabsorbing composite applications. 14 Transition metal nanoparticles, such as Ni, Co, Fe, and Au are of considerable importance for the catalytic growth of nanostructures including carbon nanotubes 11,15,16 and silicon nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoparticles and other metal nanostructures are the basic building blocks in photonics research 12 and it is expected that magnetic nanoparticles will have a dramatic impact on high density magnetic recording 13 and radarabsorbing composite applications. 14 Transition metal nanoparticles, such as Ni, Co, Fe, and Au are of considerable importance for the catalytic growth of nanostructures including carbon nanotubes 11,15,16 and silicon nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the microstructure and nanostructure of the fabricated layer, it is necessary that some parameters to be controlled. For example, the increase in the concentration of FePt colloidal solution leads to creation of a thick layer [14]. High evaporation rate of hexane solvent is a problem.…”
Section: Introductionmentioning
confidence: 99%
“…SC method is a nonequilibrium method and the controllable aspects of crystallization of colloidal solution have not yet been found [13][14][15][16]. Islands formation and surface holes are typical problems of SC method [13,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve these requirements, several studies were reported. [6][7][8][9][10][11][12][13] For example, a small grain and a high perpendicular magnetic anisotropy L1 0 phase has been observed on FePt films using multilayer deposition techniques and a rapid thermal annealing ͑RTA͒ method. In general, an annealing temperature of about 350-550°C is required.…”
Section: Introductionmentioning
confidence: 99%